Structural, Functional, and Evolutionary Characterization of Major Drought Transcription Factors Families in Maize - Mittal, Shikha; Banduni, Pooja; Mallikarjuna, Mallana G.; Rao, Atmakuri R.; Jain, Prashant A.; Dash, Prasanta K.; Thirunavukkarasu, Nepolean (Frontiers in Chemistry, 2018)
Drought is one of the major threats to maize production. In order to improve the production and to breed tolerant hybrids, understanding the genes and regulatory mechanisms during drought stress is important. Transcription factors (TFs) play a major role in gene regulation and many TFs have been identified in response to drought stress. In our experiment, a set of 15 major TF families comprising 1436 genes was structurally and functionally characterized using in-silico tools and a gene expression assay. All 1436 genes were mapped on 10 chromosome of maize. The functional annotation indicated the involvement of these genes in ABA signaling, ROS scavenging, photosynthesis, stomatal regulation, and sucrose metabolism. Duplication was identified as the primary force in divergence and expansion of TF families. Phylogenetic relationship was developed individually for each TF family as well as combined TF families. Phylogenetic analysis grouped the TF family of genes into TF-specific and mixed groups. Phylogenetic analysis of genes belonging to various TF families suggested that the origin of TFs occurred in the lineage of maize evolution. Gene structure analysis revealed that more number of genes were intron-rich as compared to intronless genes. Drought-responsive CRE’s such as ABREA, ABREB, DRE1 and DRECRTCOREAT have been identified. Expression and interaction analyses identified leaf-specific bZIP TF, GRMZM2G140355, as a potential contributor toward drought tolerance in maize. We also analyzed protein-protein interaction network of 269 drought-responsive genes belonging to different drought-related TFs. The information generated on structural and functional characteristics, expression and interaction of the drought-related TF families will be useful to decipher the drought tolerance mechanisms and to derive drought-tolerant genotypes in maize.